Rethinking career studies facilitating conversation across boundaries with the social chronology framework - Gunz, Hugh; Mayrhofer, Wolfgang 1958- (Cambridge University Press, 2018)
Careers are studied across many disciplines - particularly from the social sciences - but there is little conversation between them. Many scholars are studying the same thing in different ways, too often missing opportunities to learn from one another and draw on each other's ideas and findings to enrich their own. Gunz and Mayrhofer bridge these scholarly discourses as they explore the meaning of 'career' and answer the question: What is it that career scholars do when they study careers? The framework that emerges from this answer - the Social Chronology Framework (SCF) – vitally facilitates valuable conversations between scholars in different intellectual traditions. Building on the SCF framework, this comprehensive introduction to career studies encourages students, researchers and practitioners to identify commonalities between the topics they are studying and those examined in other fields, such as organization studies, drawing together interdisciplinary insights into career outcomes and their influencing factors
Keywords: Career development; Vocational guidance; Karriere